Preliminary study of the genetic structure of Triatoma venosa (Hemiptera: Reduviidae) using RAPO molecular markers - ESPITIA, CLAUDIA; JARAMILLO, CARLOS; AGUILERA, GERMÁN; PINTO, NÉSTOR; GUHL, FELIPE (Revista Colombiana de Entomología, 2004)
Triatoma venosa is one of the main secondary vectors of Chagas Disease in Colombia. To study its genetic structure, 30 adult individuals of T. venosa were collected in the municipalities of Somondoco (villages of Cabrera and Barreras), Guateque (villages of Llano Grande, Tincachoque, and Cantoras) and Sutatenza (villages of Sisquique, Ovejeras, el Gaque and Piedra Larga) department of Boyaca, from two different habitats (peridomestic and domestic). Genomic ONA of each individual was amplified by RAPO using 4 primers; the products were visualized after polyacrilamide gel electrophoresis followed by 6% silver staining. The dendrogram obtained after analysis with SYNTAX 2000 and RAPOPLOT software did not define a cluster for each insect population evaluated. When the binary matrix was analyzed with RAPOFST software, the Wright's Fst was 0,047 and Weir & Cockerharn's Fst was 0,056. The effective migration rate in this analysis was 5,0 under Wright's methodology and 4,2 under Weir & Cockerham's methodology. These preliminary results indicate a high mobility of the insects between the two habitats and a high genetic flow, which do not allow the establishment of genetic differentiation between the domestic and peridomestic populations analyzed.